DEVELOPMENT OF THE PASSING CONTROLLING EXERCISE MODEL IN FUTSAL FOR JUNIOR HIGH SCHOOL STUDENTS - Saputra, Setiya Yunus; Tangkudung, James A.P. (JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2015)
The purpose of this research was to develop a design of basic skill passing-controliing exercise model in futsal and to got empirical data about the effectiveness and efficiency of development of passing-controlling exercise model in futsal for junior high school students. The methods used in this research was research and development methodology from Borg and Gall, which it consist of ten steps. The subject of this research was the male students who participant in futsal extracurricular from junior high school in Malang City. The final result of this research and development were written on 28 handbook about passing-controlling exercise model in futsal for junior high school students that has been evaluated by experts, trial and revision, and the effectiveness has been tested. The implementation effectiveness of development of passing-controlling exercise model for futsal extracurricular participants was used "t-test" technique.Â  Before the data was analyzed, the normality was tested by Lilliefors test with Î± = 0.05 for pretest and posttest passing controlling futsal skills. The result of basic skill passing-controliing exercise model in futsal between pretest and posttest has tO score = 4.536 more than tt score= 1.711, so the null hypothesis was rejected, and the mean of pretest score (x1) = 11.66 smaller than the mean of posttest score (x2) = 13.53. Based on this result, it would be declared that the passing-controlling exercise model in futsal for junior high school students was effective to improve their passing-controlling skill in futsal.